Occurrence of a new mammalian tapeworm Moniezia ovisae - Humbe, Atul; Jadhav, Swati; Borde, S N (International Multidisciplinary Research Journal, 2011)
The present communication deals with the occurrence of a new mammalian tapeworm Moniezia (B) ovisae n.sp. from Ovis bharal (L) in Aurangabad (M.S.). It comes closer to all the known species of the genus Moniezia but differs from all the known species of the genus in having the scolex broad anteriorly and narrow towards neck, mature proglottids two times broader than long, testes medium in size, rounded scattered posterior to segment, 155-165 in numbers, vitelline gland post ovarian, cirrus pouch oval, Ovary is compact, bilobed.